Indonesia’s 2018 Regional Elections – Regional Setback For Jokowi? - Arifianto, Alexander Raymond (2018)
The ‘quick count’ results of the 2018 regional elections – Pilkada Serentak – show electoral setbacks for the ruling PDI-P and a strong organised campaign by the opposition Gerindra and Prosperous Justice Party (PKS). There are potential implications for the 2019 Indonesian presidential election and for President Jokowi.